The Impact of Pre-Existing Surface Texture on Laser Cladding of 316L Cladding - Ma, Chen; Du, Weilong; Yu, Zice; Zhang, Zihao; Zhao, Changlong (Manufacturing Technology Journal, 2024)
Laser cladding technology, a novel surface modification technique, is widely employed in tasks such as metal surface strengthening and repair. However, the quality post-cladding often falls short of usage requirements, harbouring defects like cracks and pores. In pursuit of a crack-free cladding method, surface texture technology is integrated with laser cladding technology to establish a multi-field coupled numerical simulation model. This model investigates the temperature, stress, and fluid fields during laser cladding with and without texture, aiming to identify the optimal cladding parameters. The results indicate that the optimal cladding parameters are a laser power of 1200 W, a scanning speed of 7 mm.s-1, and a spot radius of 2 mm. In comparison with cladding without texture, the minimum temperature has increased by approximately 50 %, while the peak temperature has remained almost unchanged. The maximum residual stress of the cladding layer without texture is 369.46 MPa, whereas that of the cladding layer with pre-set texture is 338.46 MPa, representing a reduction of approximately 8.39 %. The bottom of the cladding layer has decreased by about 29.1 %, effectively enhancing the mechanical properties at the metallurgical bond of the cladding layer. The pre-set texture induces a decreasing trend in the flow velocity inside the molten pool, eliminating the double-vortex effect, and resulting in a more uniform temperature distribution within the molten pool, consequently reducing the residual stress of the cladding layer. This paper employs multi-field coupled numerical simulation technology to monitor the internal state of the molten pool, offering insights for enhancing the quality of the cladding layer in subsequent endeavours.
Keywords: Laser cladding; Surface texture; Multi-field coupled; Residual stress